Acrodermatitis enteropathica with normal serum zinc levels: diagnostic value of small bowel biopsy and essential fatty acid determination. Issue 10 (October 1989) - Mack, D; Koletzko, B; Cunnane, S; Cutz, E; Griffiths, A
Abstract : We report a patient with acrodermatitis enteropathica and a normal serum zinc level in whom the diagnosis was confirmed by plasma phospholipid fatty acid and a small bowel biopsy response to oral zinc therapy. Acrodermatitis enteropathica is a rare autosomal recessive condition of zinc deficiency characterised by chronic diarrhoea associated with failure to thrive, periorificial dermatitis and alopecia, susceptibility to infections and behavioural changes. Diagnosis is usually established by reduced serum zinc levels (classical acrodermatitis enteropathica). Paneth cell abnormalities on electron microscope of a small bowel biopsy can be supportive. A few cases with the typical picture of acrodermatitis enteropathica without hypozincaemia (variant acrodermatitis enteropathica) have been described. The diagnosis of variant acrodermatitis enteropathica to date has been based on an entirely empiric, but nonetheless convincing clinical response to oral zinc therapy. Laboratory aids to diagnosis have been lacking.